Konsep Sehat Mental Dalam Al-Quran Menurut Hukum Negara Dan Pandangan Ulama Tafsir - Roimun, Roimun (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
Mental health is an integral part of overall health, encompassing biological, psychological, social, and spiritual aspects. The Qur'an, as the primary source of Islamic teachings, contains principles for inner healing and spiritual cleanliness, as reflected in Surah Yunus verse 57, which describes the Qur'an as an admonition (mau‘izhah), a healing (shifā’), a guidance (hudā), and a mercy (rahmah) for those who believe. This study aims to explore the meaning of mental health from the perspective of the Qur'an and its relevance to state regulations, particularly the Law of the Republic of Indonesia Number 18 of 2014 concerning Mental Health. The approach used is the maudhu’i (thematic) interpretation method along with a juridical review of national legal products. The results of the study show that the principles of spiritual healing in the Qur'an align with the principles of mental health services under Indonesian law, namely being holistic, non-discriminatory, and based on human rights. The integration of Qur'anic values into mental health services not only strengthens individual psychological resilience but also supports the national legal system in realizing a society that is healthy in both body and soul.